Positive Solutions for Some Beam Equation Boundary Value Problems. (15th November 2009) - Liu, Jinhui; Xu, Weiya
Abstract : A new fixed point theorem in a cone is applied to obtain the existence of positive solutions of some fourth-order beam equation boundary value problems with dependence on the first-order derivativeu ( i υ ) ( t ) = f ( t, u ( t ), u ′ ( t ) ), 0 < t < 1, u ( 0 ) = u ( 1 ) = u ′′ ( 0 ) = u ′′ ( 1 ) = 0, wheref : [ 0, 1 ] × [ 0, ∞ ) × R → [ 0, ∞ ) is continuous.